2004
DOI: 10.2169/internalmedicine.43.612
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Interferon-alpha in a Patient with Resistant Familial Mediterranean Fever Complicated by Polyarteritis Nodosa

Abstract: Familial Mediterranean fever (FMF) is a recurrent self-limiting polyserositis. Polyarteritis nodosa (PAN) complicating FMF is very rare. Here, we present a 17-year-old male patient with FMF who subsequently developed PAN 2 weeks after hepatitis A infection. This case was also complicated with perirenal haematoma, and right nephrectomy was performed. The clinical condition of the patient was improved after therapy with intravenous and oral corticosteroid and intravenous cyclophosphamide. However, the FMF attack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…If colchicine is ineffective this is usually due to non‐compliance, only 5% of patients are truly colchicine resistant. Both failures and successes have been reported in patients on combined colchicine and interferon‐α therapy (Tunca et al , 1997, 2004; Calguneri et al , 2004a,b). In some patients colchicine therapy has effectively been combined with infliximab ( n = 8), etanercept ( n = 2) and anakinra ( n = 2) (Aldea et al , 2004; Metyas et al , 2004; Daysal et al , 2005; Chae et al , 2006; Ozgocmen et al , 2006; Sakallioglu et al , 2006; Yuksel et al , 2006; Belkhir et al , 2007; Mor et al , 2007).…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…If colchicine is ineffective this is usually due to non‐compliance, only 5% of patients are truly colchicine resistant. Both failures and successes have been reported in patients on combined colchicine and interferon‐α therapy (Tunca et al , 1997, 2004; Calguneri et al , 2004a,b). In some patients colchicine therapy has effectively been combined with infliximab ( n = 8), etanercept ( n = 2) and anakinra ( n = 2) (Aldea et al , 2004; Metyas et al , 2004; Daysal et al , 2005; Chae et al , 2006; Ozgocmen et al , 2006; Sakallioglu et al , 2006; Yuksel et al , 2006; Belkhir et al , 2007; Mor et al , 2007).…”
Section: Treatmentmentioning
confidence: 99%
“…In some patients colchicine therapy has effectively been combined with infliximab ( n = 8), etanercept ( n = 2) and anakinra ( n = 2) (Aldea et al , 2004; Metyas et al , 2004; Daysal et al , 2005; Chae et al , 2006; Ozgocmen et al , 2006; Sakallioglu et al , 2006; Yuksel et al , 2006; Belkhir et al , 2007; Mor et al , 2007). Persistent febrile myalgia caused by vasculitis responds to systemic corticosteroids (Calguneri et al , 2004a; Gdynia et al , 2006; Soylu et al , 2006; Mor et al , 2007).…”
Section: Treatmentmentioning
confidence: 99%
“…In life-threatening cerebral vasculitis or rapidly deteriorating renal function, pulse administration of cyclophosphamide and corticosteroids should be favored. Cangüneri et al [24] presented a patient having colchicines, pulse methylprednisolone and cyclophosphamide, and redeveloped symptoms. They suggested that interferon may be a useful adjuvant for the treatment of resistant attacks in FMF patients with vasculitis.…”
Section: Discussionmentioning
confidence: 99%
“…Tekrarlayan karın ağrısı atakları, tekrarlayan pankreatit, porfi ri ile karıştırılabilir. Plevral ataklar tekrarlayan pulmoner emboli, [65]. Daha önceki gözlemlere dayanılarak AAA amiloidozuna bağlı son dönem böbrek yetmezliği olan hastalarda sürekli ayaktan periton diyalizinin abdominal atakları artırdığı ileri sürüldü [66].…”
Section: Ayırıcı Tanıunclassified